Load resistance behaviour and installation assessment of driven spun pile - Karunanidee, Vigneshwaran (2010)
Three (3) numbers of fully instrumented with global strain gauges and extensometer test Spun piles, namely PILE-A, PILE-B and PILE-C were installed using 25Ton hydraulic hammer along the coastal area which represent various subsoil conditions based on soil investigations. The static load test on instrumented piles provide more information on pile behaviour when loaded such as shaft resistance at different layer and end bearing, elastic shortening, toe movement, development of shaft and base resistance during pile displacement. This information leads to a correlation between SPT-N value and ultimate shaft and end bearing resistance. Therefore an attempt was made on this study to analyze the load test results of these instrumented spun piles to develop the correlation for subsoil at coastal area. It is assessed that the ultimate shaft friction values in the upper soft clays generally range from about 12 kPa to 20 kPa. Ultimate Shaft friction values for lower lying materials below soft clays with SPT N values from about 4 to 50 (blows/300mm) range of 2N kPa and a limiting shaft friction value of about 150 kPa. The ultimate end bearing values correlate to about 80N to 120 N kPa. Spun piles need to be closely observed during installation using hydraulic impact hammer to avoid any damages on pile and at pile joints. All the piles are fully monitored during installation using PDA analyzer and the results assessed to verify the installation technique. The assessment shows that all 3 piles were successfully installed without integrity problems. A theoretical drivability study also carried out using GRLWEAP software to provide drivability assessment and compared with actual drivability of the piles. Results from GRLWEAP is very much similar to data occurred during pile installation and confirms the drivability of spun piles at this coastal area without integrity problem. The GRLWEAP software offers variety of model and analysis option which lead to proper selection of equipments at site.